Heating and Cooling Studies of Relativistic Accretion Disks Around the Non-Rotating Black with A Simple Model - Mahboobe Moeen (Iranian Journal of Astronomy and Astrophysics, 2021)
In this paper‎, ‎the relativistic accretion disks around the non- rotating black holes are studied‎. ‎In these disks‎, we ‎study ‎the fluids with ‎influences ‎of stress ‎viscosity ‎and ‎heat ‎flux ‎in ‎the ‎ignorable ‎magnetic ‎field‎. In this paper, the reformed conservation equations with the influences of heat flux are used. We use the simple model of heat flux, in which the heat flux is proportional to temperature. Then the thermodynamic quantities are derived. We use the radial form for the radial component of four velocity in the locally non rotating frame and Keplerian angular momentum. So, the viscous heating and heat flux cooling are derived. ‎Also‎, ‎the figures of viscous heating and heat flux cooling are derived by various parameters such as the viscous coefficient and the thermal conductivity‎. Therefore, the energy balance can be study in the relativistic accretion disks. So, we see the region which have the energy balance‎.